Enhancement in strength parameters of concrete by application of Bacillus bacteria. (30th March 2019) - Nain, Nidhi; Surabhi, R.; Yathish, N.V.; Krishnamurthy, V.; Deepa, T.; Tharannum, Seema
Highlights: The bacteria Bacillus megaterium, Bacillus subtilis and their consortia showed increased compressive strength by 22.5%, 14.3% and 15.8% respectively when compared to that of conventional concrete. Concrete being weak in tension is off the point of concern, the tensile strength of concrete improved by 18.49%, 25.3% and 19.58% upon using bacteria Bacillus megaterium, Bacillus subtilis and their consortia respectively. The SEM analysis clearly depicts the presence of rhombohedral calcite crystals and acetate ions were proved by spherical crystals in the SEM images as shown in the journal. The EDAX analysis gave a higher amount of CaO content in all the 3 treated concrete specimens. Upon testing for the viability of bacteria present in concrete, by culturing them in the biotechnical laboratory. The colonies of bacteria added were found, which proved the survival of Bacillus bacteria under harsh condition. Abstract: The microbial-induced calcite precipitation (MICP) is a phenomenon of managing pre and post concrete cracks. Species like Bacillus subtilis, Bacillus megaterium and a few consortia of species have been reported to be useful to this self-healing of cracks that arise from shrinkage enhancement and settlement processes happening in concrete. This study aimed at addressing the issue of micro-crack management and also to test whether the specific microbes would augment enhancement of compressive and tensile strength of concrete. The pure cultures of the microbes along with the nutrients in requisite amounts were added in water that was an ingredient to the concrete mix. Subsequently, the blocks were cast, pond-cured for 7 and 28 days and tested for compressibility along with a test of tensile strength. The results indicate that the compressive strength and split tensile strength of the species Bacillus subtilis, Bacillus megaterium and consortia of both observed to be higher by 15% and more when compared with conventional concrete with M30 concrete in 28 days. The study conclusively indicated that the microorganism demonstrated a positive role in not only enhancing the strength of concrete but also facilitating self-healing of cracks. The bacterial application thus possesses feasibility to manage micro-cracks and enhance the strength of concrete.